2017
DOI: 10.4085/120281
|View full text |Cite
|
Sign up to set email alerts
|

On the Need to Move Toward an Evidence-Based Athletic Training (EBAT)

Abstract: Evidence-based practice (EBP) is now a well-known paradigm for the athletic training (AT) profession. The Commission on Accreditation of Athletic Training Education accredited programs have required EBP as an explicit focus for professional education, and researchers are gradually producing insightful and relevant evidence concerning the education and implementation of clinically based EBP in educational programs. Likewise, many clinicians are attempting to incorporate EBP into their daily practice in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In light of our central thesis in the evidencebased athletic training manuscript, given the considerable level of ''unknowingness'' associated with IPE outcomes and their effect on IPCP and knowing that IPE implementation is widely reported to be costly in curricular, clinical, human, and financial resources, we continue to feel that stronger and more contextually relevant evidence concerning IPE should first be secured, assessed, and consulted before we put regulations into place for all academic programs (the evidence-based regulation component of evidence-based athletic training). 1 Our commentary on IPE also brings to the table questions concerning exactly what is needed in our profession as it regards this issue. We wonder too ''what is missing'' or ''where is the void'' when it comes to athletic training's place in and within interprofessional collaboration or practice?…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…In light of our central thesis in the evidencebased athletic training manuscript, given the considerable level of ''unknowingness'' associated with IPE outcomes and their effect on IPCP and knowing that IPE implementation is widely reported to be costly in curricular, clinical, human, and financial resources, we continue to feel that stronger and more contextually relevant evidence concerning IPE should first be secured, assessed, and consulted before we put regulations into place for all academic programs (the evidence-based regulation component of evidence-based athletic training). 1 Our commentary on IPE also brings to the table questions concerning exactly what is needed in our profession as it regards this issue. We wonder too ''what is missing'' or ''where is the void'' when it comes to athletic training's place in and within interprofessional collaboration or practice?…”
mentioning
confidence: 97%
“…We thank Dr David Berry, the Editor-in-Chief of the Athletic Training Education Journal for providing us the opportunity to respond to the editorial penned by Breitbach et al 1,2 concerning 2 manuscripts we authored in volume 12, issue 2, of this journal. For clarity and simplicity, the Geisler et al paper 1 will be referred to as the evidence-based athletic training (EBAT) paper, whereas the McKeon et al paper 2 will be indicated as the knowledge paper.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6 Further, we must continue to generate, disseminate, and be guided by relevant evidence regarding best practices in all of our interconnected domains of professional practice (clinical, regulatory, and educational) to better legitimize our professional condition and position in the health care world. 7 Doing so requires ongoing, authentic, and collaborative communication; energy and creativity; and the will to negotiate and challenge the status quo in the name of progressive professional change. 8,9 Lastly, athletic training educationalists must cultivate and leverage greater academic governance over both our individual and collective futures.…”
mentioning
confidence: 99%